Molecular signatures that predict nodal metastasis in bladder cancer: does the primary tumor tell tales?. Issue 6 (June 2011) - Mitra, Anirban P; Cote, Richard J
Evaluation of: Smith SC, Baras AS, Dancik G et al. A 20-gene model for molecular nodal staging of bladder cancer: development and prospective assessment. Lancet Oncol. 12, 137––143 (2011). Accurate identification of nodal status in patients with bladder cancer is important in determining their prognosis and administration of perioperative chemotherapy. In this article, we review the study by Smith and colleagues, documenting the identification of a 20-gene model that can predict nodal stage in patients with bladder cancer based on the profiles of their primary tumors. The gene-expression model generated in this study was able to identify node-positive disease based on tumor tissues obtained from patients in a Phase III bladder cancer trial cohort. The model was able to predict nodal status independent of standard clinicopathologic prognostic criteria. This study adds the agnostic profiling dimension to prior investigations that have attempted to define molecular signatures that predict nodal metastasis in bladder cancer patients based on the primary tumors'' gene-expression profiles.